PENGELOLAAN PEMBELAJARAN MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD - Rita Sartika (Manajer Pendididikan, 2016)
This study departs from the background of the need for reform in the development of the creativity of teachers to teach mathematics in the management of the learning process as aresponse to the weakening of the quality of student learning. Through this research is expected the teachers to play a role as an innovator of learning. This research was conducted in MAN 1Bengkulu by three cycles. From the observations, student activities increased from 69% to 74% in the second cycle to 85% in the third cycle. Meanwhile, the results of daily tests showed an increase of the average - average of 5.48 on a daily test of unity becomes the average - average of 6.53 in the second daily test and be average - average 7.33 on a third daily test.Keywords: management, learning, STAD